Flight cost calculation for unmanned air vehicle based on path length and heading angle change - Sanjoy Kumar Debnath; Rosli Omar; B.S.S.K. Ibrahim; Susama Bagchi; Elia Nadira; Faisal Amin; Bashir Bala Muhammad (International Journal of Power Electronics and Drive Systems (IJPEDS), 2020)
This paper proposes a method to calculate a flight cost of an unmanned aerial vehicle (UAV) considering its change of heading angle though there are many reasons that cause the energy consumption. The proposed approach demonstrates that when a UAV moves from a starting position/point to a target/goal position/point, if the number of obstacle increases, the number of heading change would also increase. As a result, it raises the energy consumption of the UAV. It also shows that the magnitude of heading change would affect the energy consumption proportionally. The theoretical analysis as well as the simulation outcome proves the usefulness of the proposed technique.